Corruption During Non-Natural Disaster: Is Death Penalty Necessary? - Abdaud, Faisal; Sung, Ming-Hsi; Umar, Wahyudi (Jurnal Media Hukum, 2000)
Extraordinary measures are needed to combat corruption in Indonesia which has been characterised as an extraordinary crime. This includes the application of death penalty as governed in Section 2 point (2) of the Corruption Eradication Act 1999. This paper intends to analyse the implementation of the aforementioned article on corruption case that occurs during the COVID-19 outbreak. This normative legal research relies on secondary date which are collected from various sources including books, journals, related legislation. The result of the research shows that,  in regard to corruption case, the death penalty is only applicable when the corruption is committed in certain circumstances as intended in Section 2 point (2) of the Corruption Eradication Act 1999  and its amendment. These include the event of state emergency and national natural disaster. By virtue of the principle of legality, death penalty cannot be applied to the corruption cases that occurs during the national non-natural disaster like the Covid-19 pandemic. Reinterpretation of the phrase "certain circumstances" is needed for the sake of promoting justice. They should include national non-natural disasters like the Covid-19 pandemic.